2005
DOI: 10.1007/s10541-005-0220-2
|View full text |Cite
|
Sign up to set email alerts
|

Malate Dehydrogenase from the Thermophilic Bacterium Vulcanithermus medioatlanticus

Abstract: Thermostable dimeric malate dehydrogenase (MDH) was isolated from the microorganism of hydrothermal vents Vulcanithermus medioatlanticus. The enzyme was electrophoretically homogeneous and possessed the specific activity of 6.9 U/mg. The large molecular weight of the subunits (55 kD) is likely to provide the rigidity of the enzyme structure (the activation energy of the enzymatic reaction is 32.6 kJ/mol). The thermophilic MDH differs little from the mesophilic enzyme in terms of kinetic and regulatory characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The optimal pH for the MDH-dependent OAA reduction was 6.8, which agrees with the reported values from many thermophilic MDHs (30). MDH-dependent oxidation of malate is generally found to be optimal at a pH higher than that of OAA reduction.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The optimal pH for the MDH-dependent OAA reduction was 6.8, which agrees with the reported values from many thermophilic MDHs (30). MDH-dependent oxidation of malate is generally found to be optimal at a pH higher than that of OAA reduction.…”
Section: Discussionsupporting
confidence: 87%
“…The MDH from C. thermocellum was found to be thermostable, retaining over 50% activity after a 1-h incubation at 60°C. This is higher than what has been observed with the hyperthermophilic Bacillus candolyticus, which lost 50% of its activity after a 1-min incubation at 59°C, but similar to the values for Vulcanithermus medioatlanticus, which retained over 75% activity after 15 min of incubation at 60°C (30,32). The K m for OAA was significantly higher than for many characterized MDHs, such as the ones from V. medioatlanticus (0.048 mM), Corynebacterium glutamicum (0.057 mM), and Streptomyces aureofaciens (0.1 mM) (30,33,34 (33,38,39).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Earlier we established the role of MDH oligomeric forms in the adaptive reaction to different types of cultivation in the colorless sulfur bacterium Beggiatoa leptomitiformis [8,9] and in other meso-and thermophilic bacteria [10][11][12]. It was shown that MDH is a multifunctional enzyme supporting such processes as cellular respiration, TCA cycle, glyoxylate cycle, nitrogen metabolism via aspartate synthesis, osmolyte formation etc.…”
mentioning
confidence: 99%